Reasons for Discharge against Medical Advice at the Accident and Emergency Department of a Tertiary Hospital in Port Harcourt - Dabota Yvonne Buowari; Barile Edward Ikpae (Nigerian Journal of Medicine)
Introduction: Patients may at any time discontinue treatment. This is known by different names such as discharge against medical advice (DAMA) and sign against medical advice. They pose a risk to the physician and can be a source of litigation. Methodology: This is a cross-sectional study conducted at the Accident and Emergency Department of the University of Port Harcourt Teaching Hospital located in southern Nigeria. The data were collected over 34 months. Results: There are 990 study participants with 533 (53.8%) males. The number of patients that absconded is 258 (26.1%), 51 (5.2%) left before they were attended to, 7 (0.7%) left during physical examination and 2 (0.2%) left during history taking. For the reason to DAMA, no reason was given by the majority of the participants 242 (35.6%). The most common reasons are financial constraints 84 (12.4%), seeking the services of a traditional bone setter 56 (8.2%) and improved clinical state 52 (7.7%). Conclusion: The reasons for DAMA ranged from patient factors, health worker factors and health facility environment factors. Patients need to understand the reason for their actions. There needs to be enlightenment of the populace on DAMA.